Walking, waiting, interchanging. A scenario-based analysis of user requirements in local public transport. - Viergutz, Kathrin (Trialog Publishers, 2018)
This paper describes the results of an acceptance study about requirements for use of public transport. The study focused on user requirements about waiting periods at bus stops, walking distances to the destination and the acceptance of interchange connections from the point of view of different user groups. To gain these findings, a scenario-based analysis of user requirements was carried out. The aim was to determine the framework conditions under which future public mobility concepts could be used. One case of application would be demand-responsive transport concepts like ridepooling.
Keywords: Öffentlicher Verkehr; Stadtverkehr; Nahverkehr; Verkehrsmittelwahl; Bus; Fußgängerverkehr; Mobilität; Verkehrsmittel; Flexibilität; Wegelänge; Fahrzeit; Wartezeit; Nachfrageorientierung; Verkehrsangebot; Ride-Sharing; Empirische Untersuchung